2008
DOI: 10.1080/09638280701466517
|View full text |Cite
|
Sign up to set email alerts
|

The experience of owning a guide dog

Abstract: Guide dog ownership seems to be a life-changing experience, with both negative and positive consequences for the owner. Recommendations to service providers in and for the community of persons with disabilities are made in conclusion of the article, as well as suggestions given for future research on a topic of this nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 14 publications
10
56
0
Order By: Relevance
“…The research question posed was “What is the impact of volunteering to raise a guide dog puppy on human physical, psychological and social health?” The answer to this question is that there were positive and negative impacts upon self-reported human health. Like those people with vision impairment who received a guide dog [5] the experience impacted life substantially, but for the participants in this study, the impacts were more negative than positive. In this qualitative study, as opposed to the survey study by Vail [14], the costs outweighed the benefits.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The research question posed was “What is the impact of volunteering to raise a guide dog puppy on human physical, psychological and social health?” The answer to this question is that there were positive and negative impacts upon self-reported human health. Like those people with vision impairment who received a guide dog [5] the experience impacted life substantially, but for the participants in this study, the impacts were more negative than positive. In this qualitative study, as opposed to the survey study by Vail [14], the costs outweighed the benefits.…”
Section: Discussionmentioning
confidence: 83%
“…Studies on the relationship between the guide dog and the vision-impaired person are few. In a study from South Africa by Wiggett-Barnard and Steel [5] six people with vision impairment who had a guide dog were interviewed. The authors concluded that living with a guide dog was life changing and offered both positive and negative experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from disciplines outside of HCI have looked at guide dog teams. This body of work concerns itself primarily with the impact on identities of guide dog owners [19], the benefits of guide dogs [11,23], and the experience of their usage [24]. However, research on technology and guide dog teams is conspicuously absent across intersecting disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Guide-dog partners who considered their dog a satisfactory mobility aid were more mobile compared with guide-dog partners who considered their dog an unsatisfactory mobility aid, or to when they were using other mobility aids prior to acquiring their guide dogs (Lloyd et al 2008a). However, beyond being a mobility aid, acquisition of a guide dog is a life-changing event for their partners, psychologically and socially: increased selfworth, confidence, independence, social interactions, and offers from others (Sanders 2000;Whitmarsh 2005;Wiggett-Barnard and Steel 2008). These psychosocial outcomes would have synergistic effects on the increased mobility of guide dogs' partners.…”
Section: Physical Activities Of People With Visual Disabilitiesmentioning
confidence: 99%